Odyssey Self Reflection - Lotus origami / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
My childhood memory had inspired me to produce the artworks about the characteristic of lotus origami. The element in the art that I applied is the form of the origami and warm colours, meanwhile the principle in art in these artworks such as repetition, balances and systematical of the origami’s form. In sculpture, I used welding technique to form the frame’s structure so that it could hold the origami papers. In term of drawing, I applied mixed media such as charcoal and soft pastel. In Printmaking, I applied the stencil technique to produce my artwork. I used oil paint to paint my painting